Pentingnya Bukti dalam Kasus Utang Piutang - Ananda Putri Agustina Hikmawati; Jingga Ajeng Muda Jamaica; Lillah Ariani; Nataneila Astya Putri Asmana; Sahihah Anik Awalia; Heru Saputra (Universitas Wahid Hasyim, 2024)
The examination of evidence is a major factor in confirming the validity of receivables claims, ensuring compliance with legal procedures, and crafting strong arguments in court. The research on Evidence Review in Enforcement of Unpaid Receivables has several objectives, namely Investigating how evidence affects the enforcement of receivables law, identifying evidence that plays an important role, and exploring the importance of evidence examination in ensuring the success of receivables-related legal proceedings. The research method involves literature analysis, case studies, as well as the application of normative methods. Data analysis was conducted by comparing and contrasting the different types of evidence used in receivables law enforcement. The results show that in the evidentiary process related to the enforcement of unpaid receivables, an in-depth understanding of the types of evidence and their use plays a crucial role in determining the success of the legal process. With an understanding of the significant varieties of evidence and their impact on enforcement outcomes, this research can optimize the efficiency of the implementation of the enforcement process against unsettled receivables.